Comparison of the physico-chemical parameters and sensory properties of selected pasteurized meat products on Slovenian market - Polak, Tomaž (Array, 2020)
Consumers often mix pasteurised meat products from the subgroup of smoked meat with a subgroup of meat products known as canned meat. The aim of this study was therefore to determine their physicochemical parameters and sensory properties of smoked meat and canned meat subgroups of pasteurised meat products on the Slovenian market. Chemical analyses of the content of ash, sodium chloride and phosphates, thiobarbituric acid number (TBA), instrumental measurements of the proximate composition (NIR), colour (CIE L*, a*, b*) and texture (Texture Profile Analysis) as well as the evaluation of sensory properties (Descriptive Analysis Method) were performed on 33 products. The products of smoked meat had a higher content of protein, ash, total phosphates and sodium chloride than the products of canned meat. All products were oxidatively stable (low TBA number). The products of smoked meat were darker (lower L* values) and redder in cross-section (higher a* values), they were tougher, gummier, more difficult to chew, more cohesive and less elastic in texture (Texture Profile Analysis) than the products of canned meat. The panel of experts evaluated the products of both subgroups with a similar average overall impression. Compared to the products of the canned meat, the products of the smoked meat showed worse slice colour uniformity, they contained a higher level of gelatinised connective tissue on the slice, had a worse slice connectivity, the texture of a slice was firmer with coarser fibres, they were saltier, with a less pronounced metallic and rancid aroma and a more pronounced bitter, acidic and odd aroma. Chewiness, gumminess, cohesiveness, hardness and elasticity (texture parameters) loaded strongly on the quality parameters of all products (Factor analysis). Furthermore, linear discriminant analysis confirmed that the products of the subgroups smoked meat and canned meat differ in their physico-chemical and sensory profile.